The Analysis Of Effectiveness Of Student Learning Outcomes Improvement Using The Nht (Number Head Together) Learning Model - Edward Gland Tetelepta; Ferdinand Salomo Leuwol; Saparuddin Rambe; David Ranlyns Efraim Selan; Antonius Rino Vanchapo (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study is a quantitative, quasi-experimental investigation into how the Number Head Together learning approach affects students' learning outcomes. A class V student population and a "pretest-posttest control group design" were used in this investigation. The multiple-choice cognitive question used as the study's instrument was one that has undergone validity and reliability testing. The N-Gain test findings indicate that the outcomes, with a percentage score of 54%, fall into the less effective category. The findings of the Shapiro-Wilk test, which was used to test the data, revealed that they were regularly distributed. The data is homogeneous in the ANOVA test, which has a sig. of 0.980 and already exceeds 0.05. The study's findings indicate that the NHT learning model has a significant impact on students' learning outcomes if the computed t value in the independent sample test is greater than the t table and H0 is rejected and H1 is approved.